Women/Movies: Bolivia 1960-2021 - Molina Ergueta, Mary Carmen (2022)
The collective investigation “Cinema/Women: Bolivia 1960-2020” worked four spaces in the cinematographic-audiovisual cultural field in Bolivia. 1) Cineclubism and cinephilia 60/80; 2) Ukamau (Group and Producer Ldta.), production collectives and linked filmmakers; 3) Bolivian video (focus on the city of La Paz); and 4) End of the 20th century and two decades of the 21st. It opted for a new strategy for the dissemination of results and findings in the Bolivian milieu, since it carried out a museographic exhibition, book publication, talks and a cycle of films directed by Bolivian women. The research aims to contribute to the construction of new approaches to cultural history and film and audiovisual studies in Bolivia.